History Page: Leaders in MSK Radiology Hans Jessen Panner, 1871–1930 - Vanhoenacker, Filip M.; Skjennald, Arnulf (Seminars in Musculoskeletal Radiology, 2021)
This history page in the series “Leaders in MSK Radiology” is dedicated to the memory and achievements of the Danish radiologist Hans Jessen Panner, whose name is connected to the medical eponym Panner's disease.
Keywords: Panner; history; radiography